METRIC CHARACTERISTICS OF SOME TESTS FOR EVALUATION OF AEROBIC AND ANAEROBIC CAPACITIES - Slobodan Stojiljković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
This research was aimed at cheking the metric characteristics of some specific functional tests often used in practice for the evaluation of aerobic and anaerobic capacities and muscular capabilities. Keeping track of the changes and behavior of the functional abilities was performed on the basis of several repeated measurements of the same test on a sample consisting of 110 examinees, Students of the nursing school "Dr Milenko Hadzic" iz Nis, 17 years of age (± 6 months), regularly attending the classes of physical education.Two measuring instruments were tested: MARGARIA TEST and HARVARD STEP TEST.The reliability of said tests was evaluated on the basis of five successive measurements using Spearman-Brown method, based on determining of the value of the coefficients of determination of all measurements and of the main component h1.The outcome revealed high reliability of the results of most of the measurements and of the first main component H1, so that the acquired results were 91.2% for the MARGARIA TEST (anaerobic capacity) and 93.4% for5 the HARVARD STEP TEST (aerobic capacity).